The Reflection of Interreligious Coexistence on the Cultural Morphology of the Grand Omari Mosque - Shehada, Ziad M (Journal of History Culture and Art Research, 2020)
Religious monumental buildings testify to ancient history, past civilizations, and different religions. Therefore, many countries are keen to protect their monuments in various ways. History has seen many wars and conflicts among religions to extend their control over one another, reflected in their attempts to destroy religious buildings or obliterate their features. Contrastingly, areas that experienced interfaith coexistence have survived due to the smooth implementation of architectural conservation. The current research investigated the extent to which religious coexistence has affected the preservation of architectural heritage by analyzing the urban and architectural morphology of the Grand Omari Mosque in Gaza. The research applied the descriptive-historical analysis approach to identify the urban and architectural components of the mosque that have changed or have been preserved due to peaceful interreligious relationships. The research found that Islamic, Christian, Jewish, and pagan architectural elements still exist in the mosque. In each era, people preserved these elements due to the coexistence and acceptance among the religions. This resulted in the preservation of thousands of years of architectural heritage, thus preventing it from obscuration or distortion.